183k views
2 votes
-21=-3(n+4)-6(-n-2) with the steps please

User BabaVarma
by
5.3k points

2 Answers

2 votes

n = - 7

distribute the brackets on the right side of the equation and simplify

- 21 = - 3n - 12 + 6n + 12

- 21 = 3n

divide both sides by 3


(- 21)/(3) = n ⇒ n = - 7


User Chesnokov Yuriy
by
5.4k points
2 votes

-21 = -3(n + 4) - 6(-n - 2)

-21 = -3n - 12 + 6n + 12 distributed the -3 and the -6 on the right side

-21 = 3n added like terms (-3n + 6n) and (-12 + 12)


(-21)/(3) = (3n)/(3)

-7 = n

Answer: n = -7

User Alfonso Tesauro
by
5.8k points